New Human Vision Enterprise : Power Water Container / Danial Hakim Mohammad...[et al.] - Mohammad, Danial Hakim; Norman, Hafizharraz; Mohd Yusof, Muhammad Syukri; Sollahudin, Muhammad Syafiq; Abd Kamal, Farahizzatul Najwa (2019)
Thermos is the most important things for those who always do a picnic or traveler. This can be as a helpful gadget to help people to maintain the water temperature whether it cold or not. Our product is newly introduce to the Malaysia society. This product is very special because of its technology that super awesome. Our product also can used as a multitasking gadget. It is because the thermos or we named it as Power Bottle Container can heat the water inside it and also can charge the phone at the same time. This technology in the same time can save our time and energy to make the both things together. We estimate that our product is moderately acceptance among the communities in this company. This is because the product that we invented will be needed of every person in this world. At the same time, this product will be needed because every person needs to save their time to do the other importance things than to heat the water manually in the kitchen. So, we are expecting that our product can be accepted by the community that really need those technology. We are also targeting that the product can be exported worldwide. It is because, we want to introduce our brand new technology that can help people in their lifetime.